The economic value of landscapes - Heide, C. Martijn van der.; Heijman, Willem. (Routledge studies in ecological economics ;, 2013)
"This book aims to explore the avenue of landscape economics and provides the building blocks (from different scientific disciplines) for an economic analysis of landscapes. What exactly constitutes and determines the value of a landscape? It focuses on the value of landscapes in its broadest sense, thereby covering a variety of topics including stakeholder involvement in landscape design, landscape governance and landscape perceptions from different countries. Merely saying that landscapes have value or are important is not sufficient - not when resources are scarce and have alternative uses. Measuring and quantifying the economic value of changes in landscapes would help ensure that landscape management decisions are both (economically) rational and sound"--